The magnitude of standard precautions practice and its associated factors among healthcare workers in governmental hospitals of northeastern Ethiopia - Keleb, Awoke; Lingerew, Mistir; Ademas, Ayechew; Berihun, Gete; Sisay, Tadesse; Adane, Metadel (Frontiers in Health Services, 2023)
Background Non-compliance with infection control guidelines of healthcare workers may increase their risk of exposure to infectious diseases but can be prevented through adherence to standard precautionary practices in healthcare settings. Objective This study aimed to assess the magnitude of standard precautions practice and its associated factors among healthcare workers in government hospitals of South Wollo Zone, northeastern Ethiopia Methods An institutional-based cross-sectional study was conducted among 1,100 healthcare workers. Proportional sample size allocation for each selected government hospital was conducted followed by simple random sampling to select study participants using human resource records from each hospital. Data were collected using structured and self-administered pretested questionnaires. The data were analyzed using descriptive statistics, bivariable binary, and multivariable logistic regression models. Variables with a p-value <0.05 with a 95% CI were considered as having statistical significance Results The overall magnitude of compliance with standard precautions among healthcare workers was 19.2%. The result indicated that work experience of <5 years (AOR = 2.51; 95% CI: 1.07–5.89), absence of continuous water supply (AOR = 2.24; 95% CI: 1.95–5.29), and negative attitude (AOR = 2.37; 95% CI: 1.17–4.79) were significantly associated with poor compliance of standard precautions practice. Conclusion The overall magnitude of compliance with standard precautions among healthcare workers was low compared to the national magnitude of infection prevention practice. Interventions including consistent and effective training on infection prevention healthcare workers should be given regularly. Providing continuous water supply and building a positive attitude toward infection prevention practices among healthcare workers are also required.